THE INCIDENT COMMAND SYSTEM: HIGH-RELIABILITY ORGANIZING FOR COMPLEX AND VOLATILE TASK ENVIRONMENTS. - Bigley, G. A.; Roberts, K. H. (Academy of Management Journal, 2001)
The term incident command system (ICS) denotes a particular approach to assembly and control of the highly reliable, temporary organizations employed by many firefighters, police, and other public safety professionals to manage diverse resources at a wide variety of emergency scenes. Our inductive study of a fire department’s use of the ICS identified three main factors enabling this distinctively bureaucratic system to produce remarkably flexible and reliable organizations for complex and volatile task environments. In general, this research suggests the possibility of new organizational forms able to capitalize on the control and efficiency benefits of bureaucracy, while at the same time avoiding or overcoming the considerable tendencies toward inertia that are thought to accompany bureaucratic systems. Recent organization science research indicates that an expanding number of organizations are facing increasingly unforgiving socio-political-economic contexts (cf. D’Aveni, 1994). Operational failures resulting in inappropriate, incomplete, laggardly or otherwise mindless organizational responses to unexpected and demanding environmental contingencies (such as major and unforeseen competitive threats, product malfunctions and recalls, supplier collapses, technology breakdowns, etc.) are ever more likely to be immediately